Komunikowanie się z osobami z zaburzeniami osobowości borderline – trudności i wyzwania - Kubiak, Hanna; Gałczyńska, Iga (Studia Edukacyjne, 2025)
The article addresses communication difficulties in individuals with borderline personality disorder (BPD). Typical communication patterns are described, such as intense emotional reactions, fluctuating perceptions of interpersonal relationships, difficulties in emotional regulation, and fear of abandonment. Strategies supporting more effective communication with individuals with BPD are also discussed. Particular attention is given to the importance of attentive listening, creating a sense of emotional safety, applying the principles of Nonviolent Communication (NVC) and techniques promoting emotional stabilization in relationships. Practical strategies for fostering positive relationships are highlighted, both for professionals and for the family and friends of individuals with BPD